EVALUATION OF THE INTEGRATED TEACHING PROFESSIONAL PRACTICE (PPKT) PROGRAM FOR STUDENTS OF EDUCATIONAL MANAGEMENT, FITK UIN SYARIF HIDAYATULLAH JAKARTA - Mu'arif SAM (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2019)
This study aims to describe the suitability and benefits of the Integrated Teaching Professional Practice (PPKT) Program for Educational Management (EM) students in developing their competencies. The approach used is program evaluation using the Context-Input-Process-Product (CIPP) model which aims to collect accurate and comprehensive information so that it can be used to assist leaders to make further decisions to redesign, improve, or possibly stop the implementation of the program. The results showed that the PPKT program for EM students was not on target and needed to be stopped immediately or replaced with another program whose value was equivalent because: (1) Theoretically contextual, the PPKT was intended for students from study-based study programs so that it was not suitable for EM students; (2) From the Input aspect, students face the constraints of planning, implementing and evaluating learning, the weak competency of supervisors because their educational background is not from an education degree, teaching staff lack competency; (3) Based on the Process aspect, the PPKT implementation is not appropriate expected especially in teaching and research activities because the supervisor and tutor are not able to carry out their duties and functions properly; and (4) From the Product aspect, PPKT has not been able to improve teaching competence, educational research, educational creation and innovation. The acquisition of a high final score does not reflect their competence because more assessment is based on the subjectivity of tutors and tutors. Based on the results of the study, it was suggested that the Head of the EM Department need to reformulate the vision, mission and competency standards of graduates who are more referring to the competence of education staff, encouraging faculty leaders to immediately issue a decision to terminate the PPKT program for EM students and replace it with other programs with the same weight as PPKT.Keywords: context, input, process, product, PPKT.